Cyst features and risk of malignancy in intraductal papillary mucinous neoplasms of the pancreas: imaging and pathology - Grenacher, Lars; Strauß, Albert; Bergmann, Frank; Birdsey, Matthew; Mayerle, Julia (Viszeralmedizin, 2015)
Background: Intraductal papillary mucinous neoplasms (IPMNs) display diverse macroscopic, histological, and immunohistochemical characteristics with typical morphological appearance in magnetic resonance imaging. Depending on those, IPMNs may show progression into invasive carcinomas with variable frequency. Overall, IPMN-associated invasive carcinomas are found in about 30% of all IPMNs, revealing phenotpyes comparable with conventional ductal adenocarcinomas or mucinous (colloid) carcinomas of the pancreas. In Sendai-negative side-branch IPMNs, however, the annual risk of the development of invasive cancer is 2%; thus, risk stratification with regard to imaging and preoperative biomarkers and cytology is mandatory. Methods and Results: The present study addresses the radiological and interventional preoperative measures including histological features to determine the risk of malignancy and the prognosis of IPMNs. Conclusion: While preoperative imaging largely relies on the detection of macroscopic features of IPMNs, which are associated with a divergent risk of malignant behavior, in resected specimens the determination of the grade of dysplasia and the detection of an invasive component are the most important features to estimate the prognosis of IPMNs.
Gesehen am 09.11.2020